A novel method in decision making for the diagnosis of anterior urethral stricture: using methylene blue dye - KAYA, CEVDET (AVES, 2017)
Objective: The use of methylene blue dye (MB) to highlight anatomical structures in urology has been well-established. Urethral stricture may extend about a centimeter beyond the abnormal area seen on urethrogram. Although the current literature suggests a tension-free and end-to-end anastomosis after excision of the strictured urethral segment with spongiofibrosis and surrounding corpus spongiosum in short bulbar strictures, some centers dealing with urethroplasty prefer anastomosis for short bulbar strictures while others prefer augmentation. With this study, use of MB for delineating stricture line and assessing spongiofibrosis in the diagnosis of urethral stricture was evaluated. Material and methods: Five cc MB including 10 mg/mL is diluted with 10 cc saline. In the first scenario, MB is gently injected into urethra via the meatus before the urethroplasty procedure. Meanwhile, the extent of urethral segment stained by MB is noted. In the second scenario (MB spongiosography) in short bulbar stricture, insulin needles are inserted in spongiosa of the stricture site distally and proximally. MB is gently injected with distal needle. The two remaining needles are then observed. Presence of MB efflux in proximal needle implies deficiency of significant spongiofibrosis, so buccal augmentation is performed. Absence of efflux of MB implies significant spongiofibrosis and anastomotik site excised. Results: Four hundred and ninety-two consecutive cases prospectively evaluated between 2010 and 2014. Precise staining of stricture was successfully observed in 464 (94%) patients. Grossly normal appearing urothelium remained pink. Histopathology confirmed that the stained urethra had a stricture. Of the 22 short bulbar idiopathic strictures, in 18 (82%) MB was seen across the stricture and urethral transection was avoided. Anastomosis was performed in 4 (18%) cases where no MB went across the primary excision. There were no known allergic complications. Conclusion: MB aids in delineating the urethral lumen and exact site of stricture that needs augmentation. MB Spongiography in short bulbar strictures could be used as a beneficial guide in relation to the type of urethral repair to be performed in terms of augmentation versus excision and anastomosis.
Keywords: Methylene blue dye; spongiofibrosis; urethra; urethroplasty; urethral stricture; urethral reconstruction; AUGMENTED ANASTOMOTIC URETHROPLASTY; BULBAR URETHROPLASTY; RECONSTRUCTION